Estudo da independência funcional, satisfação com a tecnologia assistiva e fatores associados em pessoas com lesão medular - Tannús, Rogério Assunção (2020)
Introduction: Spinal cord injury can have a high impact on the level of physical disability. Individuals with spinal cord injuries who use an auxiliary mobility device can develop greater participation and social integration. Objective: To evaluate functional independence in activities of daily living, satisfaction with the use of assistive technology (wheelchair) and associated factors in individuals with spinal cord injury. Methods: This is a cross-sectional analytical study with a quantitative approach. The sample consisted of 146 participants with traumatic spinal cord injury with paraplegia and quadriplegia. For data collection, a sociodemographic questionnaire was used, and the Spinal Cord Independence Measure-Self Reported Version (brSCIM-SR) and the Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST 2.0) scales that allowed the investigation. Results: The average age was 37.8 years, with a majority of males (82.9%), single (52.7%), average education (53.4%), traffic accident (50%), firearm (22, 6%). There was a predominance of complete injury (58.9%) and paraplegia (65.1%). In brSCIM-SR the general average was 55.3 (± 15.8) in the self-care domain of 14.6 (± 5, 3), breathing / sphincter 26.4 (± 7.4) and mobility of 14.3 (± 5.5). In terms of satisfaction with assistive technology, the total QUEST 2.0 score was 3.64 (± 0.77), satisfaction with the resource 3.86 (± 0.74) and the provision of services 3.64 (± 0.77)). Conclusion: Good performance was identified in the average of functional independence. In addition, high levels of satisfaction with assistive technology, specifically more with the resource than with the provision of services. No correlation was found between functional independence and satisfaction with the use of AT